PARTISIPASI PEREMPUAN DALAM MUSRENBANG: PERSPEKTIF KOMUNIKASI PEMERINTAHAN - Tuty Suciaty Razak; Faidah Azuz; Suaib Ibrahim (Jurnal Pallangga Praja (JPP), 2020)
Encouraging societies to participate in developing be placed on two discussed area that namely top downand bottom up. Musrenbang is one of the implementations top down and bottom up approaches. Womenas a important element in local society have to participating in Musrenbang. This study aims to seek (1)How participation women level in Musrenbang, (2) how women entering on the steps of participating inlocal Musrenbang. Method for collecting data is quantitative approach with descriptive analysis. Locus ofresearch in two villages, Desa Tuju and Desa Pattiro. The results are (1) women participate on Musrenbangboth kader and non kader, (2) The high participating level of women in mMsrenbang is get invitation fromlocal leader (65 percent) and the lowest level of women participating is dialog with government. (3) Bycompare women participating in two villages show that in all level, women in Desa Tuju more participatingthen women in Desa Pattiro. This study also finds that for all level, local government communication needmore booster for getting women participating in Musrenbang.